A Managerial Model for Digital Curriculum Design Based on Islamic Values and Local Wisdom - Noqti Nuril Khovi; Moh. Rifa`i (Journal of Educational Management Research, 2026)
This study aims to develop an integrated digital curriculum model for Madrasah Ibtidaiyah that harmonizes technological innovation with Islamic values and local wisdom through a participatory management approach. A descriptive qualitative research design was employed, involving in-depth interviews with school leaders, teachers, and community representatives, supported by participatory observation and document analysis. Data were analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, with credibility ensured through source and methodological triangulation. The findings reveal five key outcomes: (1) digital learning practices are systematically integrated with Islamic values; (2) local wisdom is sustained through the incorporation of religious and communal traditions into digital learning content; (3) teachers play a strategic mediating role between curriculum policy, digital pedagogy, and students’ cultural contexts; (4) community collaboration strengthens the sustainability of value-based digital learning; and (5) participatory management is manifested through the active involvement of all madrasah stakeholders. The study implies that effective digital curriculum design in Islamic primary education requires managerial integration of technology, religious values, local culture, and community participation to ensure adaptive, innovative, and culturally responsive educational practices.